High‐risk symptoms do not predict gastric cancer precursors. Issue 1 (9th November 2018) - Da, Ben; Jani, Niraj; Gupta, Nikhil; Jayaram, Preeth; Kankotia, Ravi; Yao Yu, Chung; Dinis‐Ribeiro, Mario; Buxbaum, James
Abstract: Background & Study Aims: Gastric intestinal metaplasia (GIM) is the most common precursor of gastric cancer. Our aim is to determine if presenting symptoms predict gastric cancer precursor lesions in a high‐risk population. Patient and Methods: Consecutive unique patients evaluated by endoscopy for upper gastrointestinal symptoms at the Los Angeles County Hospital between 2010 and 2014 were evaluated. Presenting symptoms were classified as low‐ or high‐risk depending on the procedure indication as coded using the Clinical Outcomes Research Initiative (CORI) system. Endoscopy and histology results were used to classify findings as benign, GIM, high‐risk GIM, or malignant. The primary outcome was the proportion of patients with premalignant or malignant gastric findings who had high‐risk clinical indications for endoscopy relative to those with benign results. Results: A total of 3699 patients underwent endoscopy to evaluate upper gastrointestinal symptoms. There were 373 (10.1%) patients with GIM of which 278 had high‐risk GIM. One hundred and sixty (4.3%) patients were diagnosed with gastric cancer. High‐risk indications for upper endoscopy predicted gastric cancer (OR 1.8 [95% CI 1.3‐2.6]) but not GIM (OR 1.0 [0.8‐1.3]) or high‐risk GIM (OR 0.9 [0.7‐1.2]). Hispanic or Asian patients and patients >50 years old were more likely to have GIM, high‐risk GIM, and cancer. Conclusions: Performance of upper endoscopy for high‐risk indications is inadequate to detect GIM and marginal for malignancy. At risk patients should undergo upper endoscopy for both low‐ and high‐risk symptoms. Screening certain populations deserve additional study and may, in fact, be cost‐effective.